2003
DOI: 10.1034/j.1600-0773.2003.930103.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Actions of Diazepam and Other Phosphodiesterase Inhibitors on the Effects of Noradrenaline in Rat Myocardium

Abstract: Diazepam inhibits different isoforms of the enzyme cyclic nucleotide phosphodiesterase and also potentiates the inotropic effect of endogenous catecholamines in rat heart. In the present study we have examined whether this late effect is the consequence of inhibition of a phosphodiesterase subtype or whether inhibition of several phosphodiesterase subtypes is involved. We compared the effect of diazepam with that of the selective inhibitors of phosphodiesterase1 (MIMX), phosphodiesterase2 (EHNA), phosphodieste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…62,106 -108 In particular, it has been suggested that PDE4 inhibitors, although promoting isoprenalineinduced inotropic responses, have little effect alone. 106,109 Intriguingly, much analysis of this effect has been performed using diazepam, which has been suggested to function through PDE4 inhibition, 109 although any possible action on the "novel" cAMP-hydrolyzing PDE7/8/10/11 forms has yet to be assessed. Indeed, PDE4 inhibitors, which have potential therapeutic use in treating sepsis, improve cardiac contractility in endotoxemia, 110 suggesting that they may have a role for treating critically ill patients.…”
Section: Cardiomyocyte Pde4smentioning
confidence: 99%
“…62,106 -108 In particular, it has been suggested that PDE4 inhibitors, although promoting isoprenalineinduced inotropic responses, have little effect alone. 106,109 Intriguingly, much analysis of this effect has been performed using diazepam, which has been suggested to function through PDE4 inhibition, 109 although any possible action on the "novel" cAMP-hydrolyzing PDE7/8/10/11 forms has yet to be assessed. Indeed, PDE4 inhibitors, which have potential therapeutic use in treating sepsis, improve cardiac contractility in endotoxemia, 110 suggesting that they may have a role for treating critically ill patients.…”
Section: Cardiomyocyte Pde4smentioning
confidence: 99%
“…This resulted in increased heart rate (HR), independently from baroreflex sensitivity, which is only moderately attenuated by diazepam [8]. In isolated animal heart preparations, diazepam produced a negative inotropic effect [9], but this effect was not observed in intact animals, where diazepam induced potentiation of the cAMP-dependent positive inotropic effect of endogenous noradrenaline via the selective inhibition of phosphodiesterase 4 isoenzyme activity [10, 11]. …”
Section: Introductionmentioning
confidence: 99%
“…However, different expressions and activities of PDE enzymes in the heart have been described among species, tissues, cells and subcellular compartments (28)(29)(30). In addition, effects of PDEs inhibitors on cardiac functions has been examined in basal and stimulated conditions in different experimental models (30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%